2006
DOI: 10.1002/j.2162-6057.2006.tb01269.x
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Thinking and Evaluation Skills: Do They Always Go Together?

Abstract: The aim of the present study was to explore the hypothesized relationship between divergent thinking (DT) and two types of evaluation: interpersonal (judgments about others' ideas) and intrapersonal (judgments about one's own ideas). Divergent thinking and evaluation skills were measured by means of a GenEva (Generation and Evaluation) task. There were two conditions of the task: intrapersonal and interpersonal, and two aspects of a given idea were assessed: originality and uniqueness. The main results suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 20 publications
5
80
0
1
Order By: Relevance
“…Not surprisingly, research shows that people's top-two judgments covary strongly with the raters' judgments: people seem capable of discerning their better ideas from their worse ideas (Silvia, 2008b). But some people's top-two judgments covaried more strongly than others' judgments did, consistent with the notion that creative evaluation is a skill that varies between people (Grohman et al, 2006 andSternberg, 2006). Interestingly, we have consistently found that top-two scoring yields higher effect sizes than average scoring (Silvia et al, 2008, Study 2;) and snapshot scoring, a simple holistic scoring method ).…”
Section: Reliability Across Tasks and Scoring Methodssupporting
confidence: 83%
“…Not surprisingly, research shows that people's top-two judgments covary strongly with the raters' judgments: people seem capable of discerning their better ideas from their worse ideas (Silvia, 2008b). But some people's top-two judgments covaried more strongly than others' judgments did, consistent with the notion that creative evaluation is a skill that varies between people (Grohman et al, 2006 andSternberg, 2006). Interestingly, we have consistently found that top-two scoring yields higher effect sizes than average scoring (Silvia et al, 2008, Study 2;) and snapshot scoring, a simple holistic scoring method ).…”
Section: Reliability Across Tasks and Scoring Methodssupporting
confidence: 83%
“…To assess the remoteness of association component of creativity, people generated responses to a consequences task; the responses were scored on a 1-3 -remoteness‖ scale (Christensen et al, 1957). Since Guilford, many researchers have used subjective ratings of responses to divergent thinking tasks, such as scoring each response on a 1-5 scale (Harrington, 1975) or a 1-7 scale (Grohman, Wodniecka, & K#usak, 2006), scoring responses as high or low in quality (Harrington, Block, & Block, 1983), and scoring the full set of responses on a 1-7 scale (Mouchiroud & Lubart, 2001). …”
Section: Uniqueness Scoring Penalizes Large Samplesmentioning
confidence: 99%
“…The self and external raters’ assessments were significantly related, providing evidence that these children were modestly aware of their creativity even though they tended to underestimate it. Grohman et al () found different results with older students. They compared the ability of 100 Polish 15‐ to 17‐year‐olds to assess their own and their peers’ creative ideas for originality and uniqueness in standardised tasks against the assessment of external experts.…”
Section: Resultsmentioning
confidence: 94%